Penerapan Algoritma Maximum Marginal Relevance Dalam Peringkasan Teks Secara Otomatis - Kurniawan, Ade; Humaidy, Mohd Irsan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The search engine is a device for searching information from available documents. But the search engine will give you a lot of search results, so to find a document we have to open a meeting. Text summarization allows us to get key information from a document quickly without requiring us to read the contents of the document manually.One of the methods used is Maximum Marginal Relevance (MMR). MMR belongs to the extractive summary category (choosing the sentence in the document as the main sentence of the document content). MMR is done by weighting each sentence in the document.It is hoped that with the application of the Maximum Marginal Relevance Method this automatic summary of text can reduce the level of data redundancy and can help readers understand the meaning of the summary results and provide good information